EFEKTIVITAS PELAKSANAAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI NAGARI SIBARAMBANG - Agusman Agusman; Elimartati Elimartati (Institut Agama Islam Negeri Batusangkar, 2022)
Marriage after the marriage contract hopes to get peace, happiness. Underage marriages are marriages carried out under the age of 19. Law No. 16 of 2019 article 7 paragraph (1)